2022
DOI: 10.1186/s13098-022-00813-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating type and amount of dietary protein in relation to metabolic syndrome among Iranian adults: cross-sectional analysis of Fasa Persian cohort study

Abstract: Background and aim Metabolic syndrome is characterized by several conditions including abdominal obesity, dyslipidemia, impaired glucose levels, and hypertension; which all are directly associated with an increased risk of cardiovascular disease and type 2 diabetes mellitus. This study aimed to evaluate the association of the amount and source of dietary protein with the risk of metabolic syndrome and its components in adult men and women. Material and method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Vasbinder et al [33] also reported that higher total protein intake, specifically animal protein, was strongly associated with MetS in postmenopausal women. Conversely, Jamshidi et al [34] reported that a higher intake of total protein is associated with lower odds of having MetS in Iranian women. Lee et al [35] investigated the correlations between high fat and high protein with MetS using the KNHANES (2018-2020), but no relationship was found between them.…”
Section: Discussionmentioning
confidence: 95%
“…Vasbinder et al [33] also reported that higher total protein intake, specifically animal protein, was strongly associated with MetS in postmenopausal women. Conversely, Jamshidi et al [34] reported that a higher intake of total protein is associated with lower odds of having MetS in Iranian women. Lee et al [35] investigated the correlations between high fat and high protein with MetS using the KNHANES (2018-2020), but no relationship was found between them.…”
Section: Discussionmentioning
confidence: 95%
“…We used a validated International Physical Activity Questionnaire (IPAQ) to determine how physically active the participants were. According to the IPAQ scoring protocol, individuals were divided into the following groups in terms of physical activity: [ 1 ] low active (< 600 MET (Metabolic Equivalent of Task) -h/week); [ 2 ] moderate active (≥ 600 MET-h/week); and [ 3 ] high active (≥ 3000 MET-h/week). We also used a standard sociodemographic questionnaire to collect data on age, education level, marital status, job, supplementation, and economic status.…”
Section: Methodsmentioning
confidence: 99%
“…During the last century, our lifestyles and dietary habits have significantly changed, leading to the obesogenic environment we live in today. The growth of Western lifestyles characterizes this transition and causes an increase in overweight and obesity worldwide [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have examined the relationship between dietary macronutrients, such as protein, and CVDs, and have found significant associations [17][18][19][20]. Different types of protein may have varying effects on CVD risk factors, and substituting one type of protein for another may be beneficial in reducing certain risk factors [21][22][23][24][25][26][27][28][29][30][31]. The present study aims to investigate the effects of protein substitution on CVD risk factors.…”
Section: Introductionmentioning
confidence: 96%
“…Additionally, plant proteins such as soy protein have been shown to be effective in reducing plasma cholesterol levels [22]. However, some studies have found reverse associations or no significant relationship [26][27][28][29]. Furthermore, the substitution of different types of protein intake may also affect CVD risk factors [30][31][32].…”
Section: Introductionmentioning
confidence: 99%